A Hormone Cell Atlas maps the human endocrine system at cellular resolution - Lijiang Fei; Isabel Huang-Doran; Katherine Lawler; Yizhou Yu; Jan Patrick Pett; Kevin M. Méndez-Acevedo; Dinesh Shah; Jaume Margalef-Rieres; Joseph S. Pohlman; Batuhan Cakir; Madelyn R. Moy; Robert G. Legg; et al. (Science, 2026)
Hormones act across tissues and organs to coordinate physiological functions. Drawing inspiration from the Human Cell Atlas, we analyzed the expression of 379 hormone and receptor genes in a transcriptomic dataset comprising 14 million single cells and nuclei across 47 human tissues. Using hormone2cell, we mapped putative hormone-producing and hormone-receiving cell types, defining tissue-specific and cross-tissue endocrine signatures. We predicted nonclassical sites of hormone expression, including secretin in plasmacytoid dendritic cells, inferred convergent hormone action and endocrine feedback loops, and implicated cell populations in monogenic endocrine disorders. In a cross-tissue integration of adipocyte datasets, we uncovered dynamic endocrine programs across depots, within adipocyte subtypes and through adipogenic differentiation. Cumulatively, the Hormone Cell Atlas ( hormonecellatlas.org.uk ) provides a comprehensive framework for dissecting hormonal impact on health and disease.